The Influence of Service Quality On Behavioral Intentions with Perceived Value as An Intervening Variable at the Kok Tong Café Tebing Tinggi - Sugito, Sugito (SEAN Institute, 2024)
This research aims to determine the effect of service quality on behavioral intentions with Perceived Value as an Intervening Variable p at Café Kok Tong Tebing Tinggi. The research method used is a quantitative method using SPSS version 25.00 which was collected from the results of distributing questionnaires to 100 employees. The analytical method used in this research is using instrument tests, namely validity and reliability tests. Classic assumption tests are normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, analysis of the coefficient of determination (R2), hypothesis testing namely T test and path analysis ( Path analysis ). The results of SPSS in this research are that the service quality variable (X) influences the perceived value level variable (Z) . Service quality (X) has no effect on the behavioral intentions variable (Y). The variable perceived value (Z) influences behavioral intentions (Y), and the path analysis of equation I shows that the calculation results obtained show that the indirect influence through the perceived value level variable (Z) is greater than the direct influence on the behavioral intentions variable (Y ), then the perceived value level variable can mediate the influence of service quality on behavioral intentions.